جريمة الاخلال بالاداب العامة بواسطة وسائل تقنية المعلومات: دراسة مقارنة - د. نوفل علي الصفو; محمد عزت فاضل الطائي (PROSPECTIVE RESEARCHES, 2023)
Modern technical devices represent the most postulated phenomena of all contemporary advanced communities due to its nature which is based upon the operation of merging computer sciences with tale communications. This available modern device may lead to be as assistant factors for a certain group of crimes. Such crimes may include those which could cause serious harm to public manners by producing or sending those prohibited matters throughout the internet. Its worth mentioning that, the Iraqi legislator did not treat these above mentioned crimes through a special provision. Where as such crimes are usually adapted according to Article No.(403) of the amended Iraqi Penal Code No.(111) of 1969. This article treated the crime by a general traditional provision which did not give any importance to the very device by which the crime has been committed either it was a conventional or technical one. Therefore, the provision of Article (403) was not sufficient for convicting technical crèmes or even for putting the appropriate punishments for them. Furthers more, preparatory actions of such technical crimes are considered as the accommodation work from the corner of incriminating such crimes, whereas other penal codes considered them as executive actions which create these crimes. In addition to that another penal codes, required a special intention which is embodied by exploitation and contribution for the purpose of convicting such crimes. Other penal code required only a general intention for incriminating technical crimes. Finally, the punishment of such kind of crimes according to the Iraqi Penal Code No. (111) of 1969 does not confirm with their very nature in comparison with other Penal codes.